Restricting immigration to foster migrant integration? A comparative study across 22 European countries - Marc Helbling; Stephan Simon; Samuel D. Schmid (Journal of Ethnic and Migration Studies, 2020)
Elaborating a popular assumption about the effects of immigration policies on the integration of migrants, we argue in this article that more restrictive immigration policies lead to the selection of immigrants with greater integration potential, and that this selection should foster migrant integration. To test this argument, we combine country-level data from the Immigration Policies in Comparison (IMPIC) database with individual-level data on economic, political and social integration from multiple rounds of the European Social Survey (ESS) across 22 European countries. We show that, first, more restrictive immigration policies do not increase the likelihood of more educated migrants to be admitted, but they do make it more likely for migrants from European OECD countries to be admitted, while making it less likely for migrants outside the OECD. Second, we find that immigration policies affect some forms of economic, political and social integration outcomes, but mostly for immigrants from non-OECD countries. We conclude that immigration policies do affect integration outcomes but that these effects are small and limited to specific integration outcomes and migrants from specific regions. Our study, therefore, relativises the underlying popular assumption that immigration restrictions foster migrant integration, bearing important implications for the currently salient debates on immigration policy-making.
Keywords: 330; immigration policies; integration outcomes; Europe